Creating a Common Table: Using Peer Mediated Intervention to Promote Social Communication Skills with At-Risk and Autism Spectrum Disorder Populations - Craig-Unkefer, Lesley; Loncola Walberg, Jennifer (Journal of the American Academy of Special Education Professionals, 2015)
Identifying an intervention that is effective for multiple populations can be a challenge. Given the potential range of students in an inclusive setting, the need to identify common strategies that promote skill development for multiple populations is essential. Professionals need to identify those strategies that promote skill development that meet the needs of the individual student as well as the other students in the classroom setting. An investigation was conducted using a three-part peer mediated intervention for two distinct populations. The purpose of this investigation was to examine how consistent strategies impacted diverse participant populations in the area of social communication. Results are discussed per participant population and how targeted common strategies can promote skill development of diverse populations, including those identified as being at risk or with a diagnosed disability.